Factors affecting reductions in dietary salt consumption in people of Chinese descent: An integrative review. (5th April 2022) - Chan, Alex; Chan, Sally Wai‐chi; Khanam, Masuma; Kinsman, Leigh
Abstract: Aims: To identify and synthesize the evidence on the perceptions of the health effects of dietary salt consumption and barriers to sustaining a salt‐reduced diet for hypertension in Chinese people. Design: A systematic integrated review integrating quantitative and qualitative studies using the PRISMA guidelines. Data sources: Three databases, MEDLINE, PubMed and CINAHL, were systematically searched for articles published between January 2001 and July 2020. Review methods: The quality of the included studies was appraised using the Joanna Briggs Institute's critical appraisal tools for cross‐sectional and qualitative studies. Descriptive analysis and constant comparison methods were used to analyse the extracted data. Results: Fourteen studies met the inclusion criteria. The synthesized results identified that (i) adequate salt‐related health education had a positive influence on dietary behaviour modifications, (ii) the level of educational exposure to the health benefits of salt reduction influenced Chinese people's perceptions of the health impact associated with high salt intake, (iii) the complexity of salt measurement was a barrier to salt reduction, (iv) salt reduction is a challenge to Chinese food culture, and (v) Chinese migrants may experience linguistic and cultural challenges when they seek appropriate dietary education and advice for hypertension management in their host countries. Conclusion: There is room for improvement in recognizing and translating the knowledge of salt‐related health issues and the benefits of that knowledge about salt reduction into action. Future nursing interventions should incorporate individuals' cultural needs and the dietary culture of immediate family members. Impact: This integrative review reveals that unique Chinese customs and practices reduce the effectiveness of salt reduction campaigns. The effects of education vanish without family support, resulting in suboptimal adherence to dietary salt reduction strategies.